(untitled) (UM Museum of Anthropological Archaeology, 1973)
Grotesque Human Face On Pipe: A side view of a grotesque human face, of light colored firing, fashioned on the bowl of a pottery pipe. Approximate age is 1500. Location- Richmond Mills Site, Ontario, New York. Dimensions are 4 cm. by 4 cm.